INFLUENCE OF FACTORS IN PURCHASING HEALTH INSURANCE POLICY: A STUDY IN KHANNA CITY - Kaur, Jashanpreet; Himanshi; Ms. Harneet (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Health insurance adoption in India is influenced by multiple factors, including economic, demographic, psychological, and social determinants. This literature review examines key studies on health insurance purchase behavior, highlighting the role of income, education, awareness, risk perception, and government initiatives. Findings indicate that affordability, financial literacy, trust in insurance providers, and employer-sponsored schemes significantly impact purchase decisions. While policies like Ayushman Bharat have improved access for low-income groups, challenges such as claim settlement issues and misconceptions about insurance persist. The review emphasizes the need for increased financial education, transparency in insurance processes, and digital adoption to enhance health insurance penetration in India.